Earnings Persistence of Basic Material Companies in Terms of Book-Tax Difference, Operating Cash Flow, Accrual Component with Company Size as A Moderating Variable - Muhammad, Akhya Rizki; Restuningdiah, Nurika; Pujiningsih, Sri (Journal of Applied Business, Taxation and Economics Research, 2024)
This study aims to see the effect of book-tax difference, operating cash flow, and accrual components, on the persistence of corporate earnings in the Basic Material sector. The method used is explanatory quantitative. The analysis results show that the three independent variables have a positive influence on the level of corporate earnings persistence. In addition, the company size variable acts as a moderating variable that strengthens the relationship between operating cash flow and accrual components with earnings persistence. Furthermore, this finding indicates that companies with a larger size tend to have a higher level of earnings persistence in the face of differences between book income and tax income, operating cash flow, and accrual components. Confirmation of agency theory is also found in this study. The practical implications of this study provide insight for companies in the Basic Material sector regarding the factors that affect earnings persistence. In addition, the emphasis on the role of company size as a moderating factor can help financial managers and practitioners in managing corporate earnings by considering aspects such as the difference between book profit and tax profit, operating cash flow, and accrual components. This is especially important in the context of corporate taxation.